EARNING QUALITY AND POTENTIAL BANKRUPTCY OF ISLAMIC BANKS: INDONESIA VERSUS MALAYSIA - Grandis Imama Hendra (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2018)
This study aims to analyze the difference in earning quality and potential bankruptcy of Islamic banks before and after the adoption of IFRS and to analyze the relationship of earnings quality and potential bankruptcy to the operating cash flow of Islamic bank. Data obtained from the financial statements of 12 Islamic banks in Indonesia and 17 Islamic banks in Malaysia with financial reporting period from 2010 to 2016. Earning quality is measured by discretion of loan loss provision and the potential bankruptcy of Islamic banks is measured using the Altman z score model. The results show that the earning quality of Islamic banks did not have significant differences between before and after IFRS adoption. While Islamic banks in Malaysia have significant differences between before and after the adoption of IFRS. Islamic banks in both countries do not have the potential bankruptcy difference between before and after IFRS adoption. The earnings quality decreased when the potential bankruptcy at high levels.===================================================================Kualitas Laba dan Potensi Kebangkrutan Bank Syariah: Indonesia Versus Malaysia. Penelitian ini bertujuan untuk menganalisis perbedaan kualitas laba dan potensi kebangkrutan bank syariah sebelum dan sesudah adopsi IFRS dan untuk menganalisis hubungan kualitas laba dan potensi kebangkrutan dengan arus kas operasi bank syariah. Data diperoleh dari laporan keuangan 12 bank syariah di Indonesia dan 17 bank syariah di Malaysia dengan periode pelaporan keuangan dari 2010 hingga 2016. Kualitas laba diukur dengan diskresi cadangan kerugian pembiayaan dan potensi kebangkrutan bank syariah diukur dengan menggunakan model Altman z skor. Hasil penelitian menunjukkan bahwa kualitas laba bank syariah tidak memiliki perbedaan yang signifikan antara sebelum dan sesudah adopsi IFRS. Sementara bank syariah di Malaysia memiliki perbedaan signifikan antara sebelum dan sesudah adopsi IFRS. Bank syariah di kedua negara tidak memiliki perbedaan potensi kebangkrutan antara sebelum dan sesudah adopsi IFRS. Kualitas laba menurun ketika potensi kebangkrutan di level tinggi.